CHARACTER BUILDING OF ELT:THEORY, RESEARCH AND COMMENTARY IN INDONESIAN CONTEXT: (Membangun Karakter ELT: Teori, Penelitian Dan Komentar pada Konteks Indonesia) - Khulaifah Khulaifah (Perspektif Pendidikan dan Keguruan, 2017)
Character education is a national movement creating schools that foster ethical, responsible, and caring young people by modeling and teaching good character through emphasis on universal values that we all share. This paper is exploring how theory, research and commentary about character building of ELT in Indonesian context. By reviewing journal published, the writer come to the three worth to be discussed. When we talk about character building, we can separated to character education, then the questions will come up to 1)Can we embrace character education in schools?, 2)What is the relationship between language and character building?, 3) and Is it possible to attain ‘Moral Values’ as a result of language and character building?. Conveying foreign language as a need to tolerate and to be sensitive to differences among others become one of the moral values attained